Design of low-noise amplifier for MEMS sensors - Ng, Jing Wei (2025)
This project focuses on minimizing low-frequency noise and enhancing signal integrity from a common industrial underwater pressure sensor (MS5803-14BA), whose small signal output makes it vulnerable to noise interference. In recent years, the demand for accurate and low-noise signal acquisition in MEMS-based pressure sensing applications has grown significantly. This is especially critical in underwater environments, where the design of an efficient analog front-end is essential to ensure signal integrity. To address this, the primary objective of this project is to design a low-noise, chopper-stabilized amplifier capable of interfacing with this sensor. The proposed amplifier is implemented using Generic Process Design Kit (GPDK) 90nm CMOS technology in the Cadence Virtuoso environment. Chopper modulation is employed to suppress flicker noise by modulating the low-frequency input to a higher frequency where noise is less dominant, followed by demodulation and filtering. The design process involves modelling the sensor’s electrical characteristics, determining the required gain to fully utilize a 24-bit ADC, and constructing a signal chain that includes a Wheatstone bridge, NMOS chopper switches, a differential amplifier, and a low-pass filter. Transient simulation and post-layout analysis confirm the amplifier’s effectiveness, achieving a gain of 20.01 dB and excellent common-mode rejection of 115.4 dB. Besides, the noise analysis shows a significant reduction in input-referred noise, from 6.33019 µV to 0.712369 µV while maintaining a low average power consumption of 17.8 µW. The output is compatible with the ADC's full dynamic range, ensuring optimal resolution. This work demonstrates a complete analog front-end solution that meets the performance requirements for high-precision MEMS pressure sensor applications. Future work may focus on integrating the digital processing blocks on-chip to streamline signal processing and minimize reliance on external components.